Guidance for creating individual and batch latinized binomial virus species names - Postler, Thomas S; Rubino, Luisa; Adriaenssens, Evelien M; Dutilh, Bas E; Harrach, Balázs; Junglen, Sandra; Kropinski, Andrew M; Krupovic, Mart; Wada, Jiro; Crane, Anya; Kuhn, Jens H; Mushegian, Arcady; et al. (Journal of general virology, 2022)
The International Committee on Taxonomy of Viruses recently adopted, and is gradually implementing, a binomial naming format for virus species. Although full Latinization of these names remains optional, a standardized nomenclature based on Latinized binomials has the advantage of comparability with all other biological taxonomies. As a language without living native speakers, Latin is more culturally neutral than many contemporary languages, and words built from Latin roots are already widely used in the language of science across the world. Conversion of established species names to Latinized binomials or creation of Latinized binomials may seem daunting, but the rules for name creation are straightforward and can be implemented in a formulaic manner. Here, we describe approaches, strategies and steps for creating Latinized binomials for virus species without prior knowledge of Latin. We also discuss a novel approach to the automated generation of large batches of novel genus and species names. Importantly, conversion to a binomial format does not affect virus names, many of which are created from local languages.